2013
DOI: 10.1136/heartjnl-2013-304443
|View full text |Cite
|
Sign up to set email alerts
|

Indexing aortic valve area by body surface area increases the prevalence of severe aortic stenosis

Abstract: Background To account for differences in body size in patients with aortic stenosis, aortic valve area (AVA) is divided by body surface area (BSA) to calculate indexed AVA (AVA index ). Cut-off values for severe stenosis are <1.0 cm 2 for AVA and <0.6 cm 2 /m 2 for AVA index . Objective To investigate the influence of indexation on the prevalence of severe aortic stenosis and on the predictive accuracy regarding clinical outcome. Methods Echocardiographic and anthropometric data from a retrospective cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 17 publications
2
33
0
4
Order By: Relevance
“…6,23 Although contemporary outcome data supporting the prognostic value of AVA/BSA are scant, 9,24 US and European guidelines 1,2 have included AVA/BSA among criteria for grading AS severity (ie, AVA/BSA <0.6 cm 2 /m 2 ). In a study including 103 asymptomatic patients with, AS, AVA/BSA 24 Jander et al 9 have recently shown that among patients with AS the number of patients with AVA/BSA <0.6 cm 2 /m 2 is significantly greater than the number of patients with AVA <1 cm 2 and that the predictive accuracy for aortic valve events of the 2 parameters is almost identical. 9 Our results show that asymptomatic patients with AS in whom at the time of diagnosis AVA/BSA is <0.4 cm 2 /m 2 represent a high-risk group with >60% rate of events at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,23 Although contemporary outcome data supporting the prognostic value of AVA/BSA are scant, 9,24 US and European guidelines 1,2 have included AVA/BSA among criteria for grading AS severity (ie, AVA/BSA <0.6 cm 2 /m 2 ). In a study including 103 asymptomatic patients with, AS, AVA/BSA 24 Jander et al 9 have recently shown that among patients with AS the number of patients with AVA/BSA <0.6 cm 2 /m 2 is significantly greater than the number of patients with AVA <1 cm 2 and that the predictive accuracy for aortic valve events of the 2 parameters is almost identical. 9 Our results show that asymptomatic patients with AS in whom at the time of diagnosis AVA/BSA is <0.4 cm 2 /m 2 represent a high-risk group with >60% rate of events at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a study including 103 asymptomatic patients with, AS, AVA/BSA 24 Jander et al 9 have recently shown that among patients with AS the number of patients with AVA/BSA <0.6 cm 2 /m 2 is significantly greater than the number of patients with AVA <1 cm 2 and that the predictive accuracy for aortic valve events of the 2 parameters is almost identical. 9 Our results show that asymptomatic patients with AS in whom at the time of diagnosis AVA/BSA is <0.4 cm 2 /m 2 represent a high-risk group with >60% rate of events at 2 years. We also clearly demonstrate that in asymptomatic AS, the use of higher AVA/BSA cutoffs result in similar risk of events during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indexing the valve area may reclassify smaller individuals from severe to moderate aortic stenosis (AS), but indexing all patients, particularly with extreme obesity, can lead to substantial overestimation of severity and should not be relied upon [ 18 ].…”
Section: Additional Measurements Of Hemodynamic Severitymentioning
confidence: 99%
“…23 There are concerns about indexing aortic valve area by body surface area, as this system increases the prevalence of severe aortic stenosis cases by including patients with less advanced disease, without improving the diagnostic accuracy for valvular disease-related events. 24 This is especially important in obese patients because indexing by body surface area could clearly overestimate the severity of aortic valve stenosis. 25 A new score to predict the outcome of mitral valvuloplasty that incorporates mitral valve area 1 cm 2 , maximum leaflet displacement at diastole 12 mm, commissural area ratio 1.25, and subvalvular involvement has been validated in a large patient sample and has shown better predictive capacity than the Wilkins score.…”
Section: Valvular Heart Diseasementioning
confidence: 99%